Fluid and deformation induced partial melting and melt escape in low-temperature granulite-facies metasediments, Damara Belt, Namibia. - Ward, Robert Alexander (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Earth Sciences))--University of Stellenbosch, 2009.